PRIVATE SECTOR IN HEALTH CARE DELIVERY: A REALITY AND A CHALLENGE IN PAKISTAN - Shaikh, Babar Tasneem (Journal of Ayub Medical College Abbottabad, 2015)
Under performance of the public sector health care system inPakistanhas created a room for private sector to grow and become popular in health service delivery, despite its questionable quality, high cost and dubious ethics of medical practice. Private sector is no doubt a reality; and is functioning to plug many weaknesses and gaps in health care delivery to the poor people ofPakistan. Yet, it is largely unregulated and unchecked due to the absence of writ of the state. In spite of its inherent trait of profit making, the private sector has played a significant and innovative role both in preventive and curative service provision. Private sector has demonstrated great deal of responsiveness, hence creating a relation of trust with the consumers of health inPakistan, majority of who spend out of their pocket to buy '˜health'. There is definitely a potential to engage and involve private and non-state entities in the health care system building their capacities and instituting regulatory frameworks, to protect the poor's access to health care system. Keywords: Health care system; Health seeking behaviours; Private sector; Developing countries;Pakistan